Teachers’ Labeling of students and its effect on Students’ Self– concept: A Case of Mwala District, Machakos County, Kenya - Mwania, Jonathan M.; Muola, James M. (International Journal of Education and Research, 2013)
There is a need to help secondary school students to attain higher academic achievements in the national examinations. This is because good performance in these examinations acts as a channel through which students proceed to higher education levels and good jobs. It has been argued that persons with high self concept are more effective and do better at a given level of intelligence than persons with low self-concept. This study seeks to find out whether the way the teacher labels students affects the students’ self-concept. The study employs an ex post facto research design. The target population includes all the 360 Form Four students in the six public secondary schools in Mwala District of Machakos County. A proportionate random sample of 186 students has been selected from the six schools. Data has been collected through administration of questionnaires to the respondents. The collected data has then been processed and analyzed using both descriptive and inferential statistics with the aid of Statistical Package for Social Science (SPSS) version 16.0 for windows. The findings show that the kind of teachers’ feedback about academic performance and ability of the students influences their self-concept. The findings of this study could help teachers to boost the level of self-concept of the students and this in turn may lead to the improvement in academic performance. It could also help the Ministry of Education to see the necessity of training more teacher counselors to enhance positive self –concept in students. Lastly, it may help teachers to focus on positive feedback about academic performance and ability of students in order to encourage them to work hard. This may in turn enhance improvement in students’ performance.
Keywords: Self-concept; Labeling; Academic Performance